Role of King Salman Humanitarian Aid and Relief Centre in eliminating the effect of crises and disasters from the viewpoint of center’s employees - Alanazi, Yousef Daham (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify the role of the King Salman Center for Relief and Humanitarian Action in reducing the effects of crises and disasters, through: Identifying the reality of managing and coordinating humanitarian and relief work at the international level at the King Salman Relief and Humanitarian Center. Knowing the extent of the contribution of the King Salman Relief and Humanitarian Center in dealing with disasters and humanitarian crises. Identify the obstacles that face the King Salman Center for Relief and Humanitarian Action in managing and coordinating relief and humanitarian work, and find out whether there are statistically significant differences in the responses of the study community towards the study axes due to their variables. The method and tool of the study were: The researcher used the descriptive approach, and also used the questionnaire as a tool to collect data. The population of the current study consists of all the workers at the King Salman Humanitarian Aid and Relief Center in Riyadh, whose number is (350) employees, and the sample of the study was (234) employees, the study reached the following results: The reality of managing and coordinating the humanitarian and relief work of the King Salman Humanitarian Aid and Relief Center indicates the center’s excellence in communicating with international specialists and international organizations in light of cooperation and a common strategy. The center has an effective and significant role in mitigating the effects of disasters and crises by providing and supporting care for those directly affected, as well as by supporting relief and humanitarian organizations. The center provides its humanitarian and relief services under international humanitarian law without discrimination, whether they are racial, sectarian or racist. Humanitarian and relief work faces some obstacles that limit its effectiveness, the most important of which is the lack of transparency and cooperation by some governments affected by disasters and crises. It was found that the views of the employees in the King Salman Center on the first axis indicates (I agree) with an arithmetic average (3.96), in the second axis they contribute to a moderate degree with an arithmetic average (3.25) and in the third axis it indicates (I agree) with a mean of (4.17). In light of Results, The study recommends the following: Work to spread the culture of volunteerism more in societies through schools, universities and other community institutions. Encouraging the public and private sectors and individuals, including the center’s staff, to innovate in relief and humanitarian work, which helps the humanitarian and relief organizations to provide their services in a distinguished and rapid manner. The necessity to continuously monitor the follow-up of disasters and humanitarian crises around the world and work to urgently contribute to the provision of humanitarian and relief services to them. Work to raise awareness of the dangers and impacts of disasters and crises among individuals, organizations and charities, and qualify them to participate in facing these risks by developing plans, programs and training courses in cooperation with the concerned authorities.